Different efficacies of common disinfection methods against candida auris and other candida species - Leiwen Fu; Tingting Le; Zhihua Liu; Ling Wang; Huijie Guo; Jun Yang; Qing Chen; Jing Hu (Elsevier, 2020)
Background: Candida auris can form long-lasting colonies in the hospital environment and on human skin. There is limited evidence regarding the efficacy of different methods and products for disinfecting hospitals and colonized patients to prevent the spread of C. auris. Methods: The minimum inhibitory concentration of three disinfectant products ("84" disinfectant, IodineTincture disinfectant, and quaternary ammonium) and 75% ethanol against C. auris and other Candida species were measured. A pig skin model was used to evaluate the efficacy of three hand hygiene products in killing pathogens. The killing effect of ultraviolet-C (253.7 nm) and the LK/CXD bed unit ozone disinfection machine on C. auris was also evaluated. Results: Thirty seconds of pig skin washing with bacteriostatic hand sanitizer followed by drying and 15 s of ethanol-based gel can completely eradicate the colonization of C. auris (3.00 log10 CFU). The antifungal activity of ultraviolet-C to C. auris inoculated on bed sheets was significantly reduced (P < 0.01) at a distance of 1 m. Candida glabrata and C. auris showed greater resistance to ozone than other Candida species. The ozone could completely eradicate C. auris (3.60 log10 CFU) on bed sheets at dosage of 300 mg/m3 for 40 min of exposure. Conclusions: We recommend extending the disinfection times of ultraviolet-C and ozone and emphasizing the effectiveness of washing skin with soap, drying skin, and then applying an ethanol-based gel to remove C. auris from skin. Keywords: Candida auris, Disinfection, Infection control, Ultraviolet-C, Ozone, Hand hygiene